The State of Philippine-Iran Bilateral Relations, Maximizing Values, Human Potentials and Shared History - SEVILLA jr, Henelito A. (Historia i Świat, 2023)
The Philippines and Iran are two important players in the geopolitical transition of Asian and the Pacific region. The geopolitical values that these two countries held over many decades exposes them to rivalries and competition among regional and international powers. In some part of history, they became a closed ally to the United States, while regime change in Iran in the late 1970s had created some sort of difficulty for both countries to improve bilateral relations amidst normalization. This paper therefore seeks to investigate existing domestic and external factors that can help explain the underdeveloped state of their bilateral relations. In doing so, the paper advances the idea that although the Philippines and Iran are sovereign and independent countries, the course and direction of their relation since the post-1979 event was heavily affected by the US policy vis-à-vis the Philippines and Iran.